Algebraic thinking skills included in the mathematics textbook for middle third grade - et. al., Shorouk Salim Hadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to find out the extent to which algebraic thinking skills are included in the mathematics textbook for the third intermediate grade for the academic year (2020-2021) by answering the main research question: What algebraic thinking skills are included in the mathematics textbook for middle third grade? The descriptive and analytical approach was used, and to achieve the goal of the research, a list of the main algebraic thinking skills and the sub-skills were prepared, and after analyzing the content of the mathematics textbook, the stability of the analysis was verified through the analysis over time and across individuals using the Holsti equation, and it obtained a stability ratio of more than 82%. The research resulted in including algebraic thinking skills as a whole, but in varying proportions. The percentage of algebra skill as a language for mathematics (46.75%), algebra skill as a tool for studying functions and mathematical modeling (21.24%), representation skill (16.30%) and problem-solving skills (%) 7.01), the skill of algebra as mere arithmetic (4.52%), and the skill of inference (4.17%) (ranking). In light of these results, a number of recommendations and proposals were reached.